(untitled) (MAGNETON: Jurnal Inovasi Pembelajaran Fisika, 2025)
The low level of science literacy among Indonesian students, as reflected in the 2018 PISA scores (396, below the OECD average of 489), suggests that there are innovative learning approaches in physics. This study aims to analyse the effectiveness of implementing the problem-based learning (PBL) model for enhancing students’ scientific literacy in physics education through a systematic literature review. The method used was a literature review based on bibliometric analysis with the assistance of the Publish or Perish and VOSviewer applications. The selection process from 100 articles resulted in 9 publications (8 journals, 1 proceeding) that met the inclusion criteria (range of years 2020–2025). The research results indicate that the PBL model consistently improves science literacy, with the average N-gain increase falling into the moderate category, as seen in Fadhila’s (2022) study at 0.39 and Muladi & Suwarna’s (2024) study at 0.67. Additionally, the implementation rate of PBL based on science literacy was also high at 98.8% (Wulandari & Setiani, 2025). PBL has proven effective when applied to various physics topics such as temperature and heat, magnetic fields, and optical instruments, supported by both digital (e-LKPD, Powtoon) and non-digital learning media. The evaluation instruments used include multiple-choice tests, essays, descriptions, and combinations. The conclusions of this study indicate that PBL significantly contributes to strengthening students’ science literacy by fostering critical thinking skills, problem-solving abilities, and connections between physics concepts and real life. These findings support the integration of PBL as a primary strategy in 21st-century competency-based physics education in Indonesia.